THE EFFECT OF TEMPERATURE ON ZOOXANTHELLAE OF ISOPORA PALIFERA AND ACROPORA HYACINTHUS FROM KARANRANG ISLAND, INDONESIA - Hasanah, Alinda N; Rukminasari, Nita; Yunus, Budiman; Yanuarita, Dewi; Jompa, Jamaluddin; Suharto, Suharto; Inaku, Dwi Fajriati (Hasanuddin University, 2018)
Climate change and global warming cause massive damage to the environment. One of the major events that arethreatening the marine ecosystem is coral bleaching. Coral bleaching occurs when corals are exposed to above or belownormal temperatures. The aims of this study are to compare the resistance of Isopora palifera and Acropora hyacinthusfrom Karanrang Island to temperature stress. Four treatment temperatures (28ºC, 30ºC, 32ºC, and 34ºC) were tested toassess the role of temperature stress and bleaching to Isopora palifera and Acropora hyacinthus for 48-hours. Theabundance of zooxanthellae counted as the temperature stress variable. The results showed that there was a difference ofcoral response tothe treatment based on the time of experiment, after 48-hours experimentexposed at temperaturetreatment of 34°C the abundance of zooxanthellae from Isopora paliferawas 0,06 x105 cm-2 and the abundance ofzooxanthellae from Acropora hyacinthus is 0,18 x105cm-2. In comparison between species, Isoporapalifera taken fromKaranrang Island was more resistant to temperature stress thanAcroporahyacinthus.